STUDI DESKRIPTIF PENGETAHUAN IBU POSTPARTUM NORMAL MENGENAI MANAJEMEN LAKTASI DI PUSKESMAS PONED KABUPATEN BANJARNEGARA - Ratih Subekti; Reni Sumanti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2020)
Lactation is the whole process of breastfeeding from breast milk produced to the process of babies sucking and swallowing breast milk. The success of the breastfeeding process can be achieved by applying good lactation management. Lactation management starts from pregnancy (antenatal), immediately after giving birth (natal) and breastfeeding (post-natal). The purpose of this study was to determine the description of the knowledge of normal postpartum mothers regarding lactation management at the PONED Community Health Center in Banjarnegara District. This type of research is quantitative research with a descriptive approach. Sampling using consecutive sampling, the sample size is 60 normal postpartum mothers. Analysis of the data used is univariate analysis. In this analysis only produces a frequency distribution. The research instrument used a questionnaire sheet containing the characteristics of respondents and regarding lactation management which consisted of six indicators namely knowledge about breastfeeding, breast care, IMD, correct breastfeeding techniques, breastfeeding on demand and breast milk. The results of this study show a picture of normal postpartum maternal knowledge about lactation management with good knowledge of 20 people (33.3%), enough that is 34 people (56.7%) and less than 6 people (10.0%).